1993
DOI: 10.2527/1993.71112919x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between sex and ractopamine on protein and lipid deposition in rapidly growing pigs3

Abstract: Sixty pigs were used to investigate the effects of two levels of dietary ractopamine (RAC; 0 and 20 mg/kg) and three sex types (SEX; boars, gilts, and barrows) on performance over the live weight range 60 to 90 kg. Pigs were housed in individual pens and allowed ad libitum access to a diet containing 3.466 Mcal of DE and 10.7 g of lysine/kg. Control boars exhibited faster and more efficient growth and deposited more protein and less fat than gilts or barrows. The RAC increased ADG by 17 and 21% in gilts and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
63
4
14

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 29 publications
16
63
4
14
Order By: Relevance
“…These findings are in line with recent studies reporting a tendency towards lower ADG for entire males reared in group compared to castrates (Dunshea et al, 2001;D'Souza and Mullan, 2002;Suster et al, 2006). Contrarily, some previous studies reported that entire male pigs had higher ADG and better FCR than castrates (Whittemore et al, 1988;Campbell et al, 1989;Dunshea et al, 1993). This might be surprising as the genetic growth potential was markedly improved in the last decade due to breeding efforts.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with recent studies reporting a tendency towards lower ADG for entire males reared in group compared to castrates (Dunshea et al, 2001;D'Souza and Mullan, 2002;Suster et al, 2006). Contrarily, some previous studies reported that entire male pigs had higher ADG and better FCR than castrates (Whittemore et al, 1988;Campbell et al, 1989;Dunshea et al, 1993). This might be surprising as the genetic growth potential was markedly improved in the last decade due to breeding efforts.…”
Section: Discussionsupporting
confidence: 90%
“…Os animais que recebem o aditivo e tem em suas dietas baixos níveis de aminoácidos podem apresentar menor desempenho quando comparados aos animais que sequer recebem a ractopamina. Isso pode ser explicado pelo fato de que a ractopamina pode diminuir o consumo de ração e, consequentemente, o consumo de aminoácidos, limitando assim o potencial de resposta do animal (SCHINCKEL et al, 2003 Resultado semelhante ao obtido neste estudo para ganho de peso foi obtido por DUNSHEA et al (1993), quando avaliaram a suplementação de 20ppm de ractopamina na dieta de suínos machos inteiros, castrados e fêmeas e verificaram que a inclusão de ractopamina na dieta promoveu aumento de 21 e 17% do ganho de peso nos suínos castrados e nas fêmeas, respectivamente, enquanto que o ganho de peso dos machos inteiros não foi alterado pela inclusão de ractopamina em relação à dieta controle. De acordo com os pesquisadores, uma hipótese para essa resposta pode ter sido a limitação proteica da dieta, uma vez que os machos inteiros apresentaram aumento de 15% na deposição diária de proteína na carcaça, enquanto que os machos castrados e as fêmeas apresentaram aumento superior a 40% na deposição proteica diária em função da inclusão de ractopamina na dieta.…”
Section: Resultsunclassified
“…Contudo, não afeta a qualidade da carne suína em termos de cor, marmoreio, firmeza e pH (HERR et al, 2000). Vários estudos (DUNSHEA et al, 1993;UTTARO et al, 1993e WILLIAMS et al, 1994 têm avaliado o efeito da inclusão de ractopamina na dieta em função do sexo dos suínos. De uma maneira geral, constata-se que a ractopamina propicia respostas semelhantes em termos de taxa de crescimento, consumo de ração e deposição de tecido muscular na carcaça, tanto em machos castrados como em fêmeas (UTTARO et al, 1993).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In pigs, as in many other domestic species, entire males are generally more muscular, less fat and more metabolically efficient than females or physical castrates (barrows; Dunshea et al, 1993). Despite these advantages, however, the traditional practice in most countries is to physically castrate male piglets early in life.…”
Section: Introductionmentioning
confidence: 99%